TECHNICAL TRAINING OF INNOVATIVE YOUNG PLAYERS IN INCREASING THE IMPORTANCE OF TECHNOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this graduating work, there are given some methods of football game in terms of, game football game tactic, the use of tactics on magnetic boards, development of tactical systems and modern tactic systems. Besides that, electron module of subject is performed. In that module, the text of the report, pedagogical technologies used in football lessons, topic tests, control tasks, presentation slides, developing tasks of tactical training are illustrated. The conclusion is about the latter recommendation and practical advice.